2018
DOI: 10.1021/acs.jchemed.8b00378
|View full text |Cite
|
Sign up to set email alerts
|

Buffers in Context: Baby Wipes As a Buffer System

Abstract: An understanding of buffers is important in a variety of chemistry subdisciplines, with relevant applications to the life sciences and health profession-related fields. Here, we describe the development and implementation of a lab that involves creating a buffer solution using baby wipes and deionized water. The goal of this lab was to emphasize a conceptual understanding of buffers within a context that would be interesting and relevant for students in a nonmajors general chemistry course, a population compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…2−7 A few of these studies included assessments of student learning. 4−7 For example, effective student understanding was reported by Barreto et al 4 after intervention with "Khan style" videos in a biochemistry course and by Rodriguez et al 5 after an experiment using baby wipes to prepare a buffer. Another study showed an increase in correct buffer answers after a guided inquiry laboratory involving discussion of pooled class data.…”
Section: Literature Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…2−7 A few of these studies included assessments of student learning. 4−7 For example, effective student understanding was reported by Barreto et al 4 after intervention with "Khan style" videos in a biochemistry course and by Rodriguez et al 5 after an experiment using baby wipes to prepare a buffer. Another study showed an increase in correct buffer answers after a guided inquiry laboratory involving discussion of pooled class data.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Most published reports concerning learning of buffer concepts are laboratory experiment or classroom innovations. A few of these studies included assessments of student learning. For example, effective student understanding was reported by Barreto et al after intervention with “Khan style” videos in a biochemistry course and by Rodriguez et al . after an experiment using baby wipes to prepare a buffer.…”
Section: Introductionmentioning
confidence: 99%
“…17 preparation of solutions with fixed pH values, students also prepared several buffer solutions, which gave them an opportunity to master this important skill. 18,19 This laboratory experiment helps students integrate concepts from acid/base equilibria, acid/base buffers, and spectrophotometry to experimentally visualize the regions where different forms of a diprotic acid are predominant.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Specifically, students used the absorbance spectra of 15 solutions, each at integer pH values in the pH range 0–14 to determine the relative abundance of different protonation forms of thymol blue. Because this experiment requires the preparation of solutions with fixed pH values, students also prepared several buffer solutions, which gave them an opportunity to master this important skill. , This laboratory experiment helps students integrate concepts from acid/base equilibria, acid/base buffers, and spectrophotometry to experimentally visualize the regions where different forms of a diprotic acid are predominant.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent works have addressed more advanced topics. , Laboratories have been developed that describe phenomena, calculations, or familiar products . Our work is unique in its focus on p K a conceptualization and use of experimental evidence to support molecular-level representations.…”
Section: Introductionmentioning
confidence: 99%